Thermosetting resin composition for printed wiring boards, prepregs, laminates, printed wiring boards and semiconductor packages
The thermosetting resin composition, featuring a phosphonium salt and a maleimide compound, addresses the challenges of heat resistance, thermal expansion, and adhesion in printed wiring boards and semiconductor packages by enhancing curing efficiency and storage stability.
Patent Information
- Application Number
- JP2022212603
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2022-12-28
- Publication Date
- 2025-04-30
- Estimated Expiration
- 2038-07-25
AI Technical Summary
Existing thermosetting resin compositions for printed wiring boards and semiconductor packages face challenges in achieving excellent heat resistance, low thermal expansion, high elastic modulus, high adhesion strength, and desmear resistance, particularly when using polyimide resins.
A thermosetting resin composition containing a phosphonium salt with a carboxylate anion as a counter ion and a maleimide compound with at least two N-substituted maleimide groups, which acts as a curing accelerator and improves the resin's properties.
The composition achieves excellent heat resistance, low thermal expansion, high elastic modulus, high adhesion strength, and desmear resistance, while also allowing for sufficient curing at lower temperatures and maintaining storage stability at room temperature.
Smart Images

Figure 0007670048000001 
Figure 0007670048000002 
Figure 0007670048000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a thermosetting resin composition for printed wiring boards, a prepreg, a laminate, a printed wiring board, and a semiconductor package. [Background technology]
[0002] In recent years, with the trend toward smaller electronic devices and higher performance, printed wiring boards have become more highly integrated and the wiring density has increased, which has led to increased demand for improved reliability through improvements in the heat resistance of wiring laminates, etc. In particular, warping caused by the difference in thermal expansion coefficient between the chip and the substrate during component mounting and package assembly has become a major issue for semiconductor package substrates. For these reasons, printed wiring boards and semiconductor packages are required to have excellent heat resistance, low thermal expansion, and a high elastic modulus.
[0003] Epoxy resins are known to have excellent dimensional stability, chemical resistance, moisture absorption resistance, and electrical insulation, and are used in wiring board materials, sealing materials, adhesives, paints, etc. However, since epoxy resins have a large thermal expansion coefficient, attempts are made to lower the thermal expansion coefficient by selecting an epoxy resin having an aromatic ring and by increasing the loading of an inorganic filler such as silica (see, for example, Patent Document 1). It is possible to further reduce the thermal expansion coefficient by loading a high proportion of inorganic filler, but it is known that increasing the loading amount of inorganic filler causes a decrease in insulation reliability due to moisture absorption, a lack of adhesion between the resin composition layer and the wiring layer, and press molding defects. On the other hand, polyimide resins have excellent strength, heat resistance, and low thermal expansion compared to other polymer resin materials, and also have excellent electrical insulation, but have a problem of low adhesive strength, which may cause problems such as peeling off and disconnection of wiring due to warping that occurs during mounting.
[0004] Furthermore, in the process of manufacturing a multilayer printed circuit board, after forming a via hole by drilling or laser processing, smears adhering to the inside and outside of the hole are treated with a desmear solution containing a permanganate solution or the like. In this case, if the thermosetting resin has low desmear resistance, the resin in the via hole is also scraped off at the same time, causing large irregularities, resulting in poor connection and requiring more gold plating, which increases costs. Therefore, the thermosetting resin used in the multilayer printed circuit board is required to have excellent desmear resistance. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Japanese Patent Application Publication No. 5-148343 Summary of the Invention [Problem to be solved by the invention]
[0006] As described above, printed wiring boards and semiconductor packages are required to have excellent heat resistance, low thermal expansion, high elastic modulus, high adhesive strength, desmear resistance, and the like. However, there is a limit to the improvement of these properties depending on the type of thermosetting resin, and it is not necessarily easy to satisfy the requirements for high adhesive strength and desmear resistance in a thermosetting resin composition containing a polyimide resin.
[0007] Therefore, an object of the present invention is to provide a thermosetting resin composition for printed wiring boards that contains a polyimide resin and that has excellent heat resistance, low thermal expansion property, and high elastic modulus as well as high adhesive strength and desmear resistance. [Means for solving the problem]
[0008] Means for Solving the Problems The present inventors have conducted intensive research to solve the above problems, and as a result have found that a thermosetting resin composition containing a specific curing accelerator and a specific maleimide compound can solve the above problems, thereby completing the present invention.
[0009] That is, the present invention provides the following [1] to [9]. [1] A thermosetting resin composition for printed wiring boards, comprising (a) a phosphonium salt having a carboxylate anion as a counter ion, and (b) a maleimide compound having at least two N-substituted maleimide groups. [2] The thermosetting resin composition for printed wiring boards according to the above [1], wherein the component (a) contains a phosphonium salt consisting of a phosphonium cation represented by the following general formula (a1) and an anion residue of a polycarboxylic acid represented by any one of the following general formulas (a2) to (a4): [ka] (In formula (a1), R 1 ~R 4 each independently represents an alkyl group having 1 to 16 carbon atoms or a substituted or unsubstituted phenyl group. [ka] (In formula (a2), R 5 is a methylene group or an ethylene group, R 6 ~R 9 each independently represents a hydrogen atom, an alkyl group having 1 to 4 carbon atoms, or a carboxyl group. [ka] (In formula (a3), R 10 ~R 13 each independently represents a hydrogen atom, an alkyl group having 1 to 4 carbon atoms, or a carboxyl group. [ka] (In formula (a4), R 14 is an alkyl group having 1 to 10 carbon atoms. n is an integer of 0 to 2. [3] The thermosetting resin composition for printed wiring boards according to the above [1] or [2], further comprising a thermoplastic elastomer (c). [4] The thermosetting resin composition for printed wiring boards according to any one of the above [1] to [3], further comprising a thermosetting resin (d). [5] The thermosetting resin composition for printed wiring boards according to any one of the above [1] to [4], further comprising an inorganic filler (f). [6] A prepreg comprising the thermosetting resin composition for printed wiring boards according to any one of [1] to [5] above. [7] A laminate comprising the prepreg according to [6] above. [8] A printed wiring board comprising the laminate described in [7] above. [9] A semiconductor package comprising the printed wiring board according to [8] above and a semiconductor element mounted thereon. Effect of the Invention
[0010] According to the present invention, it is possible to provide a thermosetting resin composition for printed wiring boards that can provide high adhesive strength and desmear resistance together with excellent heat resistance, low thermal expansion and high elastic modulus. Furthermore, the thermosetting resin composition for printed wiring boards of the present invention has excellent curability at low temperatures (about 180 to 200°C) and also has excellent storage stability (latency) at room temperature, despite containing a polyimide resin that tends not to cure sufficiently unless the temperature is high, such as 220°C or higher. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] In the numerical ranges described in this specification, the upper or lower limit of the numerical range may be replaced with the values shown in the examples. The lower and upper limits of the numerical ranges may be arbitrarily combined with the lower or upper limit of other numerical ranges, respectively. In addition, each of the components and materials exemplified in this specification may be used alone or in combination of two or more types, unless otherwise specified. The present invention also includes any combination of the features described in this specification.
[0012] [Thermosetting resin composition for printed wiring boards] The thermosetting resin composition for printed wiring boards of the present invention (hereinafter also simply referred to as the "thermosetting resin composition") contains a phosphonium salt (a) having a carboxylate anion as a counter ion [hereinafter also simply referred to as the "phosphonium salt (a)" or the "(a) component)] and a maleimide compound (b) having at least two N-substituted maleimide groups [hereinafter also referred to as the "maleimide compound (b)" or the "(b) component)].
[0013] <Phosphonium salt (a) with carboxylate anion as counter ion> The component (a) is not particularly limited as long as it is a phosphonium salt having a carboxylate anion as a counter ion, and all are included. The component (a) is preferably one in which the phosphonium cation and the carboxylate anion are in a ratio of 1 mole to 1 mole or 2 moles to 1 mole. The component (a) may be used alone or in combination of two or more kinds. By using the component (a), it is possible to improve the high adhesive strength and desmear resistance while maintaining sufficient heat resistance, low thermal expansion, and high elastic modulus. Furthermore, by using the component (a), the following advantages are also obtained. Generally, polyimide resins, for example, the maleimide compound of the component (b) used in the present invention, tend not to be sufficiently cured unless the temperature is high, such as 220°C or higher. However, by using the component (a), it is possible to sufficiently cure at low temperatures (about 180 to 200°C) (hereinafter, this characteristic may be referred to as "low-temperature curing property"). In this way, a curing accelerator that can be sufficiently cured at low temperatures has high activity, and therefore, the storage stability (latency) of the thermosetting resin composition at room temperature tends to deteriorate. However, this does not occur in the present invention using the component (a), and the storage stability (latency) at room temperature is also excellent.
[0014] As the component (a), a commercially available product can also be used. From the viewpoints of heat resistance, low thermal expansion, high elastic modulus, high adhesive strength, desmear resistance, low-temperature curing property and storage stability, it is preferable to contain, for example, a phosphonium salt consisting of a phosphonium cation represented by the following general formula (a1) and an anion residue of a polycarboxylic acid represented by any one of the following general formulas (a2) to (a4). Note that the polycarboxylic acid represented by the following general formula (a2) or (a3) is classified as an aliphatic polycarboxylic acid, and the polycarboxylic acid represented by the following general formula (a4) is classified as an aromatic polycarboxylic acid.
[0015] [ka] (In formula (a1), R 1 ~R 4 each independently represents an alkyl group having 1 to 16 carbon atoms or a substituted or unsubstituted phenyl group.
[0016] [ka] (In formula (a2), R 5 is a methylene group or an ethylene group, R 6 ~R 9 each independently represents a hydrogen atom, an alkyl group having 1 to 4 carbon atoms, or a carboxyl group.
[0017] [ka] (In formula (a3), R 10 ~R 13 each independently represents a hydrogen atom, an alkyl group having 1 to 4 carbon atoms, or a carboxyl group.
[0018] [ka] (In formula (a4), R 14 is an alkyl group having 1 to 10 carbon atoms. n is an integer of 0 to 2.
[0019] In the formula (a1), R 1 ~R 4 each independently represents an alkyl group having 1 to 16 carbon atoms or a substituted or unsubstituted phenyl group. R 1 ~R 4 Examples of the alkyl group having 1 to 16 carbon atoms represented by include a linear alkyl group having 1 to 16 carbon atoms and a branched alkyl group having 1 to 16 carbon atoms. The number of carbon atoms in the alkyl group is preferably 1 to 10, more preferably 1 to 6, and further preferably 3 to 6. Examples of the alkyl group include a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, a sec-butyl group, an isobutyl group, a tert-butyl group, an n-pentyl group, an n-hexyl group, an n-octyl group, an n-decyl group, and an n-dodecyl group. Among these, an n-butyl group is preferred, and particularly, R 1 ~R 4 It is more preferable that all of are n-butyl groups.
[0020] R 1 ~R 4 In the substituted or unsubstituted phenyl group represented by the formula (1), examples of the substituent of the substituted phenyl group include an alkyl group having 1 to 10 carbon atoms and an alkoxyl group having 1 to 10 carbon atoms. Examples of the alkyl group having 1 to 10 carbon atoms include a linear alkyl group having 1 to 10 carbon atoms and a branched alkyl group having 1 to 10 carbon atoms. The number of carbon atoms in the alkyl group is preferably 1 to 6, more preferably 1 to 4, and even more preferably 1. Examples of the alkyl group include a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, a sec-butyl group, an isobutyl group, and a tert-butyl group. Among these, a methyl group is preferred. Examples of the alkoxyl group having 1 to 10 carbon atoms include those in which the alkyl group moiety is exemplified as the alkyl group having 1 to 10 carbon atoms. The number of carbon atoms in the alkoxyl group is preferably 1 to 6, more preferably 1 to 4, and even more preferably 1. A methoxy group is preferred as the alkoxyl group. As the substituted or unsubstituted phenyl group, among the above, a phenyl group, a 4-methylphenyl group, and a 4-methoxyphenyl group are preferable, a phenyl group is more preferable, and in particular, R 1 ~R 4 It is more preferable that all of are phenyl groups. In particular, R 1 ~R 4 is preferably an n-butyl group or a phenyl group, and R 1 ~R 4 are all n-butyl groups or R 1 ~R 4 More preferably, all of R are phenyl groups. 1 ~R 4 It is more preferable that all of are n-butyl groups.
[0021] Specific examples of the phosphonium cation represented by the general formula (a1) include, for example, tetra-n-butylphosphonium cation, tetraphenylphosphonium cation, tetrakis(4-methylphenyl)phosphonium cation, tetrakis(4-methoxyphenyl)phosphonium cation, phenyltris(4-methylphenyl)phosphonium cation, phenyltris(4-methoxyphenyl)phosphonium cation, phenyltributylphosphonium cation, (4-methylphenyl)triphenylphosphonium cation, (4-methoxyphenyl)triphenylphosphonium cation, butyltriphenylphosphonium cation, etc. Among these, tetra-n-butylphosphonium cation and tetraphenylphosphonium cation are preferred, and tetra-n-butylphosphonium cation is more preferred.
[0022] The anion residue of the polycarboxylic acid represented by any one of the general formulae (a2) to (a4) refers to a carboxyl anion resulting from the removal of a hydrogen atom from a carboxyl group. For example, the anion residue of the polycarboxylic acid represented by the general formula (a2) or (a3) may be a monovalent or divalent (preferably monovalent) carboxyl anion resulting from the removal of a hydrogen atom from one carboxyl group in the polycarboxylic acid represented by the general formula (a2) or (a3). In addition, the anion residue of the polycarboxylic acid represented by the general formula (a4) may be a divalent carboxyl anion resulting from the removal of hydrogen atoms from two carboxyl groups in the polycarboxylic acid represented by the general formula (a4), more specifically, a divalent carboxyl anion resulting from the removal of hydrogen atoms from the 1-position and the 4- or 5-position carboxyl groups in the polycarboxylic acid represented by the general formula (a4).
[0023] In the general formula (a2), R 5 is a methylene group or an ethylene group, R 6 ~R 9 each independently represents a hydrogen atom, an alkyl group having 1 to 4 carbon atoms, or a carboxyl group. R 5 is preferably a methylene group. R 6 ~R 9 Examples of the alkyl group having 1 to 4 carbon atoms represented by include a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, a sec-butyl group, an isobutyl group, and a tert-butyl group. Among these, a methyl group is preferable. R 6 ~R 9 is preferably a hydrogen atom or a methyl group. In particular, from the viewpoints of heat resistance, low thermal expansion, high elastic modulus, high adhesive strength, desmear resistance, low-temperature curing property and storage stability, the anion residue of the polycarboxylic acid represented by the general formula (a2) is preferably 5 is a methylene group, and R 6 ~R 9 is an anionic residue of a polycarboxylic acid, all of which are hydrogen atoms; or (ii) R 5 is a methylene group, and R6 ~R 9 and the remaining three are hydrogen atoms; or (iii) a mixture of the anionic residues of these polycarboxylic acids.
[0024] In the general formula (a3), R 10 ~R 13 each independently represents a hydrogen atom, an alkyl group having 1 to 4 carbon atoms, or a carboxyl group. R 10 ~R 13 Examples of the alkyl group having 1 to 4 carbon atoms represented by include a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, a sec-butyl group, an isobutyl group, and a tert-butyl group. Among these, a methyl group is preferable. R 10 ~R 13 is preferably a hydrogen atom, a methyl group, or a carboxyl group. In particular, from the viewpoints of heat resistance, low thermal expansion, high elastic modulus, high adhesive strength, desmear resistance, low-temperature curing property and storage stability, the anion residue of the polycarboxylic acid represented by the general formula (a3) is preferably R 10 ~R 13 is an anion residue of a polycarboxylic acid in which all atoms are hydrogen atoms, or R 10 ~R 13 Two of them (especially R 11 and R 12 is preferably a carboxyl group and the remaining two are hydrogen atoms, and is an anion residue of an alicyclic polycarboxylic acid, 10 ~R 13 is more preferably an anion residue of a polycarboxylic acid in which all of are hydrogen atoms.
[0025] In the general formula (a4), R 14is an alkyl group having 1 to 10 carbon atoms. The number of carbon atoms in the alkyl group is preferably 1 to 6, and more preferably 1 to 4. Examples of the alkyl group include a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, a sec-butyl group, an isobutyl group, a tert-butyl group, an n-pentyl group, an n-hexyl group, an n-octyl group, an n-decyl group, and an n-dodecyl group. Among these, a methyl group is preferred. n is an integer of 0 to 2, preferably 0 or 1, and more preferably 0. When n is 2, two R 14 may be the same or different. When n is 0, R 14 is not substituted on the benzene ring, and in this case, the polycarboxylic acid represented by general formula (a4) is pyromellitic acid.
[0026] (Method for producing phosphonium salt (a)) The (a) component can be produced by a known method. For example, when using an anion residue of a polycarboxylic acid represented by the general formula (a2) or (a3), it can be produced by referring to the method described in JP-A-2015-63661, etc. When using an anion residue of a polycarboxylic acid represented by the general formula (a4), it can be produced by referring to the method described in WO 2018 / 021548, etc.
[0027] In the case of the phosphonium salt (a) having an anion residue of a polycarboxylic acid represented by the general formula (a2) or (a3), for example, a solution of a tetra-substituted phosphonium halide (solvent: water, methanol, etc.) is first ion-exchanged to obtain a solution of a tetra-substituted phosphonium hydroxide (solvent: water, methanol, etc.), and then, in the solution, 1 mole of the obtained tetra-substituted phosphonium hydroxide is neutralized with 0.5 to 5 moles (more preferably 0.5 to 2 moles) of a polycarboxylic acid represented by the general formula (a2) or (a3) to form a salt. The solvent is removed from the reaction mixture containing the obtained salt, for example by distillation under reduced pressure, to separate the target salt. If necessary, it is preferable to increase the purity by recrystallization. The above tetra-substituted phosphonium hydroxide may be a commercially available product. In addition, instead of the polycarboxylic acid represented by the general formula (a2) or (a3), the corresponding polycarboxylic acid anhydride may be used. The salt obtained by this method usually consists mainly of a salt of 1 mole of a phosphonium cation and 1 mole of an anion residue of a polycarboxylic acid.
[0028] On the other hand, in the case of the phosphonium salt (a) having an anion residue of a polycarboxylic acid represented by the general formula (a4), for example, a method of forming a salt by synthesizing a dialkali metal salt of a polycarboxylic acid represented by the general formula (a4) by a conventional method (solvent is water, methanol, etc.), and then charging 1 mole of a tetra-substituted phosphonium halide for 0.5 moles of the dialkali metal salt of the polycarboxylic acid and reacting them, etc., can be mentioned. In this case, the tetra-substituted phosphonium halide and the dialkali metal salt of the polycarboxylic acid may be used alone, or two or more of them may be used in combination to form a salt. When two or more are used in combination, for example, two or more tetra-substituted phosphonium halides and one dialkali metal salt of a polycarboxylic acid may be mixed together to form two or more bis(tetra-substituted phosphonium) dihydrogen pyromellitates, or two or more bis(tetra-substituted phosphonium) dihydrogen pyromellitates may be produced separately and then simply mixed. Alternatively, a salt may be formed by neutralizing 1 mole of the tetra-substituted phosphonium hydroxide with 0.5 moles of a polycarboxylic acid represented by general formula (a4) or an anhydride thereof. For the purpose of precipitating high purity crystals from the obtained reaction product and removing unreacted raw materials and by-produced inorganic salts, the obtained reaction product may be washed with water, an alcohol-based organic solvent, a ketone-based organic solvent, an ether-based organic solvent, a mixed solvent thereof, or the like, and may be recrystallized as necessary. The above-mentioned tetra-substituted phosphonium halide, tetra-substituted phosphonium hydroxide, polycarboxylic acid, polycarboxylic anhydride, and solvent may all be commercially available products. The salt obtained by this method usually consists mainly of a salt of 2 moles of a phosphonium cation and 1 mole of a divalent anion residue of a polycarboxylic acid.
[0029] (Structure of phosphonium salt (a)) In the phosphonium salt composed of the phosphonium cation represented by the general formula (a1) and the anion residue of a polycarboxylic acid represented by the general formula (a2) or (a3), the salt of 1 mole of the phosphonium cation, which is the main component, and 1 mole of the anion residue of the polycarboxylic acid is represented by the following general formula (I). [ka] (In formula (I), R 1 ~R 4 R in the general formula (a1) 1 ~R 4 is the same as
[0030] In general formula (I), X - represents an anion residue (monovalent anion residue) of at least one polycarboxylic acid selected from the group consisting of the alicyclic polycarboxylic acid represented by the general formula (a2) and the alicyclic polycarboxylic acid represented by the general formula (a3). That is, in the general formula (I), X represents a carboxyl anion (-COO - ) is an anionic residue.
[0031] In addition, in the phosphonium salt consisting of the phosphonium cation represented by the general formula (a1) and the anion residue of a polycarboxylic acid represented by the general formula (a4), a salt consisting of 2 moles of the phosphonium cation as the main component and 1 mole of the divalent anion residue of a polycarboxylic acid is represented by the following general formula (II). [ka] (In formula (II), R 1 ~R 4 R in the general formula (a1) 1 ~R 4 is the same as R 14 and n is R in the general formula (a1). 14 and n.)
[0032] In the general formula (II), the anion portion represents an anion residue (divalent anion residue) of a polycarboxylic acid represented by formula (a4), and strictly speaking, is an anion residue in which a carboxyl group and a carboxyl anion present across an o-phenylene chain among a plurality of carboxyl groups or carboxyl anions are coordinated to a phosphonium cation. In this case, the carboxyl group and the carboxyl anion are actually equivalent.
[0033] From the viewpoints of improving high adhesive strength and desmear resistance while maintaining sufficient heat resistance, low thermal expansion property, and high elastic modulus, the content of the phosphonium salt (a) in the thermosetting resin composition is preferably 0.01 to 3 parts by mass, more preferably 0.05 to 1.5 parts by mass, even more preferably 0.1 to 1.0 part by mass, and particularly preferably 0.1 to 0.7 parts by mass, relative to 100 parts by mass of the resin component in the thermosetting resin composition. In this specification, the resin component refers to the above-mentioned components (a) and (b) and the components (c) and (d) which are blended as necessary, and does not include the inorganic filler (f).
[0034] <Maleimide compound (b) having at least two N-substituted maleimide groups> The maleimide compound (b) is not particularly limited as long as it is a maleimide compound having at least two N-substituted maleimide groups. The maleimide compound (b) is preferably a maleimide compound having two N-substituted maleimide groups, and more preferably a compound represented by the following general formula (b-1).
[0035] [ka] (In general formula (b-1), X b1 is a group represented by the following general formula (b1-1), (b1-2), (b1-3) or (b1-4).
[0036] [ka] (In general formula (b1-1), R b1 each independently represents an aliphatic hydrocarbon group having 1 to 5 carbon atoms or a halogen atom; and p is an integer of 0 to 4.
[0037] [ka] (In general formula (b1-2), R b2 and R b3 Each of X is independently an aliphatic hydrocarbon group having 1 to 5 carbon atoms or a halogen atom. b2 represents an alkylene group having 1 to 5 carbon atoms, an alkylidene group having 2 to 5 carbon atoms, an ether group, a sulfide group, a sulfonyl group, a carbonyloxy group, a keto group, a single bond, or a group represented by the following general formula (b1-2-1): q and r each independently represent an integer of 0 to 4.
[0038] [ka] (In general formula (b1-2-1), R b4 and R b5 Each of X is independently an aliphatic hydrocarbon group having 1 to 5 carbon atoms or a halogen atom.b3 represents an alkylene group having 1 to 5 carbon atoms, an alkylidene group having 2 to 5 carbon atoms, an ether group, a sulfide group, a sulfonyl group, a carbonyloxy group, a keto group, or a single bond. s and t each independently represent an integer of 0 to 4.
[0039] [ka] (In general formula (b1-3), n1 is an integer of 1 to 10.)
[0040] [ka] (In general formula (b1-4), R b6 and R b7 are each independently a hydrogen atom or an aliphatic hydrocarbon group having 1 to 5 carbon atoms, and u is an integer of 1 to 8.
[0041] In the general formula (b1-1), R b1 Examples of the aliphatic hydrocarbon group represented by include a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, an isobutyl group, a t-butyl group, and an n-pentyl group. The aliphatic hydrocarbon group is preferably an aliphatic hydrocarbon group having 1 to 3 carbon atoms, and more preferably a methyl group. Examples of the halogen atom include a fluorine atom, a chlorine atom, a bromine atom, and an iodine atom. Among the above, R b1 is preferably an aliphatic hydrocarbon group having 1 to 5 carbon atoms. p is an integer of 0 to 4, and from the viewpoint of availability, is preferably an integer of 0 to 2, more preferably 0 or 1, and further preferably 0. When p is an integer of 2 or more, a plurality of R b1 They may be the same or different.
[0042] In the general formula (b1-2), R b2 and R b3 The aliphatic hydrocarbon group having 1 to 5 carbon atoms and the halogen atom represented by R b1The aliphatic hydrocarbon group is preferably an aliphatic hydrocarbon group having 1 to 3 carbon atoms, more preferably a methyl group or an ethyl group, and further preferably an ethyl group. X b2 Examples of the alkylene group having 1 to 5 carbon atoms represented by include a methylene group, a 1,2-dimethylene group, a 1,3-trimethylene group, a 1,4-tetramethylene group, a 1,5-pentamethylene group, etc. From the viewpoints of heat resistance and low thermal expansion, the alkylene group is preferably an alkylene group having 1 to 3 carbon atoms, and more preferably a methylene group. X b2 Examples of the alkylidene group having 2 to 5 carbon atoms represented by include an ethylidene group, a propylidene group, an isopropylidene group, a butylidene group, an isobutylidene group, a pentylidene group, an isopentylidene group, etc. Among these, an isopropylidene group is preferred from the viewpoints of heat resistance and low thermal expansion. X b2 Among the above options, alkylene groups having 1 to 5 carbon atoms and alkylidene groups having 2 to 5 carbon atoms are preferred. More preferred ones are as described above. Each of q and r is independently an integer of 0 to 4, and from the viewpoint of availability, each is preferably an integer of 0 to 2, more preferably 0 or 2. When q or r is an integer of 2 or more, a plurality of R b2 R b3 They may be the same or different.
[0043] In the general formula (b1-2-1), R b4 and R b5 The aliphatic hydrocarbon group having 1 to 5 carbon atoms and the halogen atom represented by R b2 and R b3 The same can be mentioned as in the above, and the preferred ones are also the same. X b3 The alkylene group having 1 to 5 carbon atoms and the alkylidene group having 2 to 5 carbon atoms represented by the above X b2 The alkylene group having 1 to 5 carbon atoms and the alkylidene group having 2 to 5 carbon atoms represented by the formula (I) can be mentioned, and the preferred ones are also the same. Xb3 Among the above options, alkylidene groups having 2 to 5 carbon atoms are preferred, and the more preferred ones are as described above. Each of s and t is an integer of 0 to 4, and from the viewpoint of availability, each is preferably an integer of 0 to 2, more preferably 0 or 1, and further preferably 0. When s or t is an integer of 2 or more, a plurality of R b4 R b5 They may be the same or different. The general formula (b1-2-1) is preferably represented by the following general formula (b1-2-1').
[0044] [ka] (X in general formula (b1-2-1') b3 , R b4 , R b5 , s and t are the same as those in general formula (b1-2-1), and the preferred values are also the same.
[0045] The group represented by the general formula (b1-2) is preferably a group represented by the following general formula (b1-2'), more preferably a group represented by any of the following (b1-i) to (b1-iii), and even more preferably a group represented by the following (b1-i) or (b1-iii).
[0046] [ka] (X in general formula (b1-2') b2 , R b2 , R b3 , q and r are the same as those in general formula (b1-2), and the preferred values are also the same.)
[0047] [ka]
[0048] In the general formula (b1-3), n is an integer of 1 to 10, and from the viewpoint of availability, is preferably an integer of 1 to 5, and more preferably an integer of 1 to 3. In the general formula (b1-4), R b6 and R b7 The aliphatic hydrocarbon group having 1 to 5 carbon atoms represented by R b1 The same can be mentioned as in the above, and the preferred ones are also the same. u is an integer of 1 to 8, preferably an integer of 1 to 3, and more preferably 1.
[0049] In the general formula (b-1), X b1 may be any of the groups represented by the general formula (b1-1), (b1-2), (b1-3) or (b1-4) above, and among these, from the viewpoints of low warpage, dimensional stability, heat resistance and easy availability, it is preferable that it is a group represented by the general formula (b1-2) or (b1-3).
[0050] Specific examples of the maleimide compound (b) include bis(4-maleimidophenyl)methane, polyphenylmethane maleimide, bis(4-maleimidophenyl)ether, bis(4-maleimidophenyl)sulfone, 3,3'-dimethyl-5,5'-diethyl-4,4'-diphenylmethane bismaleimide, 4-methyl-1,3-phenylene bismaleimide, m-phenylene bismaleimide, 2,2-bis[4-(4-maleimidophenoxy)phenyl]propane, etc. These may be used alone or in combination of two or more. Among these, from the viewpoint of high reactivity and ability to achieve higher heat resistance, bis(4-maleimidophenyl)methane, bis(4-maleimidophenyl)sulfone, 3,3'-dimethyl-5,5'-diethyl-4,4'-diphenylmethane bismaleimide, and 2,2-bis[4-(4-maleimidophenoxy)phenyl]propane are preferred, from the viewpoint of solubility in a solvent, 3,3'-dimethyl-5,5'-diethyl-4,4'-diphenylmethane bismaleimide, bis(4-maleimidophenyl)methane, and 2,2-bis[4-(4-maleimidophenoxy)phenyl]propane are more preferred, and from the viewpoint of production costs, bis(4-maleimidophenyl)methane and 2,2-bis[4-(4-maleimidophenoxy)phenyl]propane are even more preferred.
[0051] The content of the maleimide compound (b) in the thermosetting resin composition is preferably 30 to 90 parts by mass, more preferably 35 to 85 parts by mass, and even more preferably 40 to 70 parts by mass, relative to 100 parts by mass of the resin component in the thermosetting resin composition, from the viewpoints of low warpage, dimensional stability, low thermal expansion, low elasticity, heat resistance, and adhesive strength to a metal circuit.
[0052] (Amino-modified siloxane compound (x1)) From the viewpoint of suppressing warpage and improving dimensional stability, the thermosetting resin composition for printed wiring boards of the present invention may contain an amino-modified siloxane compound (x1). Alternatively, the amino-modified siloxane compound (x1) may be reacted with the component (b) to obtain a siloxane-modified polyimide [hereinafter referred to as siloxane-modified polyimide (X)], which may be used in place of the component (b) (from this viewpoint, the siloxane-modified polyimide (X) is a subordinate concept of the component (b)), and may be used in combination with the component (b). The amino-modified siloxane compound (x1) and the siloxane-modified polyimide (X) will be described in detail below in that order.
[0053] The amino-modified siloxane compound (x1) is preferably a siloxane compound having two primary amino groups. The amino-modified siloxane compound (x1) may have a primary amino group at either or both of the side chain or the end of the siloxane skeleton, and from the viewpoints of availability and low warpage, it is preferable that the primary amino group is at the end, and more preferably at both ends (hereinafter, a siloxane compound having primary amino groups at both ends is also referred to as a "double-end amino-modified siloxane compound"). From the same viewpoint, the amino-modified siloxane compound (x1) is preferably represented by the following general formula (x1-1).
[0054] [ka] (In general formula (x1-1), R x1 , R x2 , R x3 and R x4 Each of X independently represents an alkyl group, a phenyl group, or a substituted phenyl group. x1 and X x2 each independently represents a divalent organic group, and m is an integer of 1 to 50.
[0055] In general formula (x1-1), R x1 , R x2 , R x3 and R x4 Examples of the alkyl group represented by include a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, an isobutyl group, a t-butyl group, an n-pentyl group, etc. The alkyl group is preferably an alkyl group having 1 to 5 carbon atoms, more preferably an alkyl group having 1 to 3 carbon atoms, and further preferably a methyl group. Examples of the substituent that the phenyl group has in the substituted phenyl group include an alkyl group having 1 to 5 carbon atoms, an alkenyl group having 2 to 5 carbon atoms, and an alkynyl group having 2 to 5 carbon atoms. Examples of the alkyl group having 1 to 5 carbon atoms include the same as those described above. Examples of the alkenyl group having 2 to 5 carbon atoms include a vinyl group and an allyl group. Examples of the alkynyl group having 2 to 5 carbon atoms include an ethynyl group and a propargyl group. Among the above, R x1 , R x2 , Rx3 and R x4 As the alkyl group, a methyl group or a phenyl group is preferable. X x1 and X x2 Examples of the divalent organic group represented by include an alkylene group, an alkenylene group, an alkynylene group, an arylene group, -O-, or a divalent linking group formed by combining these groups. Examples of the alkylene group include alkylene groups having 1 to 10 carbon atoms, such as a methylene group, an ethylene group, or a propylene group. Examples of the alkenylene group include alkenylene groups having 2 to 10 carbon atoms. Examples of the alkynylene group include alkynylene groups having 2 to 10 carbon atoms. Examples of the arylene group include arylene groups having 6 to 20 carbon atoms, such as a phenylene group or a naphthylene group. m is an integer of 1 to 50, preferably an integer of 4 to 46, and more preferably an integer of 10 to 42. When m is an integer of 2 or more, a plurality of R x1 R x2 They may be the same or different.
[0056] The amino-modified siloxane compound (x1) may be a commercially available product. For example, examples of the (x1) component having a methyl group on the side chain include "KF-8010" (amino functional group equivalent: 430 g / mol), "X-22-161A" (amino functional group equivalent: 800 g / mol), "X-22-161B" (amino functional group equivalent: 1,500 g / mol), "KF-8012" (amino functional group equivalent: 2,200 g / mol), "KF-8008" (amino functional group equivalent: 5,700 g / mol), and "X-22-9409" (amino functional group equivalent: 700 g / mol) (all manufactured by Shin-Etsu Chemical Co., Ltd.). Examples of the (x1) component having a phenyl group in the side chain include "X-22-1660B-3" (amino functional group equivalent: 2,200 g / mol) (manufactured by Shin-Etsu Chemical Co., Ltd.), "BY-16-853U" (amino functional group equivalent: 460 g / mol), "BY-16-853" (amino functional group equivalent: 650 g / mol), and "BY-16-853B" (amino functional group equivalent: 2,200 g / mol) (all manufactured by Toray Dow Corning Co., Ltd.). These may be used alone or in combination of two or more. Among these, from the viewpoint of low water absorption, "X-22-161A", "X-22-161B", "KF-8012", "KF-8008", "X-22-1660B-3", and "BY-16-853B" are preferred, and from the viewpoint of low thermal expansion, "X-22-161A", "X-22-161B", "KF-8012", and "X-22-1660B-3" are more preferred.
[0057] The functional group equivalent of the amino group in the component (x1) is preferably 300 to 3,000 g / mol, more preferably 400 to 2,500 g / mol, and even more preferably 600 to 2,300 g / mol.
[0058] When the thermosetting resin composition contains the amino-modified siloxane compound (x1), the content thereof is preferably 8 to 50 parts by mass, more preferably 8 to 45 parts by mass, and even more preferably 10 to 40 parts by mass, relative to 100 parts by mass of the resin component in the thermosetting resin composition, from the viewpoints of low warpage, dimensional stability, low thermal expansion, low elasticity, heat resistance, and adhesive strength with a metal circuit.
[0059] Next, the siloxane-modified polyimide (X) is obtained by reacting the component (x1) with the component (b), and contains a structural unit (x1') derived from the component (x1) and a structural unit (b') derived from the component (b). There is no particular restriction on the method for reacting the (x1) component with the (b) component. From the viewpoints of productivity and allowing the reaction to proceed sufficiently, the reaction temperature is preferably 70 to 200° C., more preferably 80 to 150° C., and even more preferably 100 to 130° C. In addition, there is no particular restriction on the reaction time, but it is preferably 0.5 to 10 hours, and more preferably 1 to 6 hours.
[0060] The reaction between the (x1) component and the (b) component is preferably carried out in an organic solvent. Examples of the organic solvent include alcohol-based solvents such as ethanol, propanol, butanol, methyl cellosolve, butyl cellosolve, and propylene glycol monomethyl ether; ketone-based solvents such as acetone, methyl ethyl ketone, methyl isobutyl ketone, and cyclohexanone; ester-based solvents such as ethyl acetate and γ-butyrolactone; ether-based solvents such as tetrahydrofuran; aromatic solvents such as toluene, xylene, and mesitylene; nitrogen-containing solvents such as dimethylformamide, dimethylacetamide, and N-methylpyrrolidone; and sulfur-containing solvents such as dimethylsulfoxide. These may be used alone or in combination of two or more. Among these, from the viewpoint of solubility, cyclohexanone, propylene glycol monomethyl ether, methyl cellosolve, and γ-butyrolactone are preferred, and from the viewpoints of low toxicity and high volatility that make it unlikely to remain as a residual solvent, cyclohexanone, propylene glycol monomethyl ether, and dimethylacetamide are preferred, and propylene glycol monomethyl ether is more preferred. The amount of the organic solvent used is not particularly limited, but from the viewpoints of solubility and reaction rate, the amount is preferably 25 to 1,000 parts by mass, more preferably 40 to 500 parts by mass, and even more preferably 50 to 200 parts by mass, per 100 parts by mass of the total of the (x1) component and the (b) component.
[0061] After the reaction is completed, the reaction mixture obtained is mixed with other components without any particular purification of the reaction product, thereby preparing a thermosetting resin composition containing the siloxane-modified polyimide (X).
[0062] In the above reaction, the ratio of the components (x1) and (b) used is preferably such that the equivalent of the maleimide group in the component (b) exceeds the equivalent of the primary amino group in the component (x1) from the viewpoints of preventing gelation and heat resistance. That is, the ratio of the equivalent of the maleimide group in the component (b) to the equivalent of the primary amino group in the component (x1) [(b) / (x1)] is preferably greater than 1, more preferably 2 to 35, and even more preferably 10 to 35.
[0063] When the thermosetting resin composition of the present invention contains the siloxane-modified polyimide (X), the content thereof is preferably 40 to 95 parts by mass, more preferably 50 to 85 parts by mass, per 100 parts by mass of the resin component in the thermosetting resin composition.
[0064] The content of the structural unit (x1') in the siloxane-modified polyimide (X) is preferably 8 to 50 mass%, more preferably 10 to 45 mass%, and even more preferably 12 to 40 mass%, from the viewpoints of low warpage, dimensional stability, low thermal expansion, low elasticity, heat resistance, and adhesive strength to a metal circuit. The content of the structural unit (b') in the siloxane-modified polyimide (X) is preferably 50 to 92 mass%, more preferably 55 to 90 mass%, and even more preferably 60 to 88 mass%, from the viewpoints of low warpage, dimensional stability, low thermal expansion, low elasticity, heat resistance, and adhesive strength to a metal circuit. The suitable contents of the structural unit (x1') and the structural unit (b') in the thermosetting resin composition based on 100 parts by mass of the solid content of the resin component in the thermosetting resin composition are the same as the suitable aspects of the contents of the (x1) component and the (b) component in the thermosetting resin composition. However, when the thermosetting resin composition further contains one or more selected from the group consisting of the component (x1) and the component (b) in addition to the siloxane-modified polyimide (X), it is preferable that the total content of each component and the structural units derived from each component is a suitable embodiment of the content of the component (x1) and the component (b) in the thermosetting resin composition.
[0065] <Thermoplastic elastomer (c)> The thermosetting resin composition of the present invention may further contain a thermoplastic elastomer (c). Examples of the thermoplastic elastomer (c) include styrene-based thermoplastic elastomers, olefin-based thermoplastic elastomers, urethane-based thermoplastic elastomers, polyester-based thermoplastic elastomers, polyamide-based thermoplastic elastomers, acrylic-based thermoplastic elastomers, silicone-based thermoplastic elastomers, and derivatives thereof. These are composed of hard segment components and soft segment components, and the former generally contributes to heat resistance and strength, while the latter generally contributes to flexibility and toughness. These may be used alone or in combination of two or more. Among these, styrene-based thermoplastic elastomers and acrylic-based thermoplastic elastomers are preferred, and acrylic-based thermoplastic elastomers are more preferred.
[0066] The styrene-based thermoplastic elastomer is preferably a thermoplastic elastomer having a structural unit derived from styrene represented by the following general formula (c-1).
[0067] [ka]
[0068] Examples of structural units other than the styrene-derived structural units contained in the styrene-based thermoplastic elastomer include butadiene-derived structural units, isoprene-derived structural units, maleic acid-derived structural units, maleic anhydride-derived structural units, etc. These may be contained alone or in combination of two or more kinds. The butadiene-derived structural unit and the isoprene-derived structural unit are preferably hydrogenated. When hydrogenated, the butadiene-derived structural unit is a mixed structural unit of ethylene units and butylene units, and the isoprene-derived structural unit is a mixed structural unit of ethylene units and propylene units.
[0069] From the viewpoints of low thermal expansion, adhesive strength with metal circuits, heat resistance, elastic modulus, and high-frequency characteristics, the styrene-based thermoplastic elastomer is preferably at least one selected from the group consisting of hydrogenated styrene-butadiene-styrene block copolymers and hydrogenated styrene-isoprene-styrene block copolymers, and more preferably hydrogenated styrene-butadiene-styrene block copolymers. Hydrogenated styrene-butadiene-styrene block copolymers include SEBS, in which the hydrogenation rate of carbon-carbon double bonds is usually 90% or more (preferably 95% or more), and SBBS, in which the carbon-carbon double bonds at the 1,2-bond sites in the butadiene blocks are partially hydrogenated (the hydrogenation rate relative to the total carbon-carbon double bonds is approximately 60 to 85%). Among these, SEBS is more preferred.
[0070] The thermoplastic elastomer (c) may have a reactive functional group at least in the molecular terminal or in the molecular chain. Examples of the reactive functional group include an epoxy group, a hydroxyl group, a carboxyl group, an amino group, an amide group, an isocyanato group, an acrylic group, a (meth)acrylic group, and a vinyl group. By having a reactive functional group, the compatibility with other resin components is improved, and the internal stress generated during the curing of the thermosetting resin composition can be more effectively reduced, and as a result, the warpage of the printed wiring board and the semiconductor package can be significantly reduced. In particular, from the viewpoint of low thermal expansion and adhesive strength with a metal circuit, it is preferable to have one or more selected from the group consisting of an epoxy group, a hydroxyl group, a carboxyl group, an amino group, and an amide group, and from the viewpoint of heat resistance and insulation reliability, it is more preferable to have one or more selected from the group consisting of an epoxy group and a carboxyl group.
[0071] The acrylic thermoplastic elastomer is a polymer formed of molecules containing at least a structural unit derived from an acrylic acid ester. The acrylic thermoplastic elastomer contains structural units derived from a plurality of different acrylic acid esters in the molecule, and may further contain structural units derived from monomers other than acrylic acid esters. The acrylic thermoplastic elastomer may also be composed of structural units derived from a plurality of acrylic acid esters.
[0072] Specific examples of acrylate esters include methyl acrylate, ethyl acrylate, propyl acrylate, isopropyl acrylate, butyl acrylate, isobutyl acrylate, t-butyl acrylate, pentyl acrylate, hexyl acrylate, cyclohexyl acrylate, octyl acrylate, decyl acrylate, lauryl acrylate, and benzyl acrylate. Examples of the monomer other than acrylic acid ester include vinyl monomers other than acrylic acid ester, such as acrylonitrile, acrylamide, acrylic acid, methacrylic acid, methacrylic acid ester, styrene, ethylene, propylene, butadiene, etc. The monomer other than acrylic acid ester may be one type or two or more types.
[0073] The acrylic thermoplastic elastomer preferably has the reactive functional group at least either at the molecular end or in the molecular chain. In particular, from the viewpoint of adhesion to the metal foil, the reactive functional group that the acrylic thermoplastic elastomer may have is preferably an epoxy group, a hydroxyl group, a carboxyl group, an amino group, or an amide group, and from the viewpoint of heat resistance and insulation reliability, an epoxy group, a hydroxyl group, or an amino group is more preferable, and an epoxy group is even more preferable.
[0074] The weight average molecular weight (Mw) of the acrylic thermoplastic elastomer is not particularly limited, but is preferably 10,000 to 2,000,000, more preferably 50,000 to 1,200,000, further preferably 100,000 to 900,000, and particularly preferably 500,000 to 900,000. If the weight average molecular weight (Mw) is 10,000 or more, it tends to be easy to maintain a low elastic modulus, and if it is 2,000,000 or less, it tends to have good compatibility and flowability.
[0075] When the thermosetting resin composition contains the thermoplastic elastomer (c), the content thereof is preferably 0.1 to 50 parts by mass, more preferably 2 to 30 parts by mass, further preferably 5 to 30 parts by mass, and particularly preferably 10 to 30 parts by mass, relative to 100 parts by mass of the resin components in the thermosetting resin composition, from the viewpoints of improving compatibility with other resin components and effectively exhibiting low cure shrinkage and low thermal expansion properties of the cured product.
[0076] <Thermosetting resin (d)> The thermosetting resin composition may further contain a thermosetting resin (d), provided that the thermosetting resin (d) does not contain the component (b) or the siloxane-modified polyimide (X). Examples of the thermosetting resin (d) include epoxy resins, phenolic resins, unsaturated imide resins (but not including the component (b)), cyanate resins, isocyanate resins, benzoxazine resins, oxetane resins, amino resins (but not including the component (x1)), unsaturated polyester resins, allyl resins, dicyclopentadiene resins, silicone resins, triazine resins, and melamine resins. These may be used alone or in combination of two or more. Among these, from the viewpoints of moldability and electrical insulation, and adhesive strength with metal circuits, one or more selected from the group consisting of epoxy resins and cyanate resins are preferred, and epoxy resins are more preferred.
[0077] Examples of epoxy resins include bisphenol A type epoxy resins, bisphenol F type epoxy resins, bisphenol S type epoxy resins, phenol novolac type epoxy resins, cresol novolac type epoxy resins, α-naphthol / cresol novolac type epoxy resins, bisphenol A novolac type epoxy resins, bisphenol F novolac type epoxy resins, stilbene type epoxy resins, triazine skeleton-containing epoxy resins, fluorene skeleton-containing epoxy resins, triphenol methane type epoxy resins, biphenyl type epoxy resins, xylylene type epoxy resins, biphenyl aralkyl type epoxy resins, naphthalene type epoxy resins, dicyclopentadiene type epoxy resins, alicyclic epoxy resins, polyfunctional phenols and diglycidyl ether compounds of polycyclic aromatics such as anthracene, and phosphorus-containing epoxy resins obtained by introducing phosphorus compounds into these. These may be used alone or in combination of two or more. Among these, biphenyl aralkyl type epoxy resins and α-naphthol / cresol novolac type epoxy resins are preferred from the viewpoint of heat resistance and flame retardancy.
[0078] When the thermosetting resin composition contains the thermosetting resin (d), the content thereof is preferably 1 to 45 parts by mass, more preferably 2 to 40 parts by mass, further preferably 5 to 35 parts by mass, and particularly preferably 10 to 35 parts by mass, relative to 100 parts by mass of the solid content of the resin component in the thermosetting resin composition.
[0079] <Curing accelerator (e) other than the component (a)> The thermosetting resin composition may further contain a curing accelerator (e) other than the component (a) (hereinafter, also simply referred to as curing accelerator (e)). Examples of the curing accelerator (e) include organic metal salts such as zinc naphthenate, cobalt naphthenate, tin octylate, cobalt octylate, bisacetylacetonate cobalt (II), trisacetylacetonate cobalt (III), etc.; imidazoles and derivatives thereof; organic phosphorus compounds other than the component (a); secondary amines; tertiary amines; quaternary ammonium salts, etc. These may be used alone or in combination of two or more. The curing accelerator (e) may be a commercially available product, such as isocyanate mask imidazole (manufactured by Daiichi Kogyo Seiyaku Co., Ltd., product name: G-8009L) or triphenylphosphine triphenylborane (manufactured by Hokko Chemical Industry Co., Ltd., product name: TPP-S). When the thermosetting resin composition contains the curing accelerator (e), the content thereof is preferably 5 parts by mass or less, more preferably 1 part by mass or less, and even more preferably 0.5 parts by mass or less, relative to 100 parts by mass of the resin component in the thermosetting resin composition, from the viewpoint of not inhibiting the effects of the present invention provided by the component (a). However, it is most preferable that the thermosetting resin composition does not contain the curing accelerator (e).
[0080] <Inorganic filler (f)> The thermosetting resin composition may further contain an inorganic filler (f). Examples of the inorganic filler (f) include silica, alumina, titanium oxide, mica, beryllia, barium titanate, potassium titanate, strontium titanate, calcium titanate, aluminum carbonate, magnesium hydroxide, aluminum hydroxide, aluminum silicate, calcium carbonate, calcium silicate, magnesium silicate, silicon nitride, boron nitride, clay such as calcined clay, talc, aluminum borate, silicon carbide, quartz powder, glass short fiber, glass fine powder, hollow glass, etc. Examples of glass include E glass, T glass, D glass, etc. These may be used alone or in combination of two or more. Among these, silica is preferred from the viewpoints of dielectric properties, heat resistance, and low thermal expansion. Examples of silica include precipitated silica produced by a wet method and having a high water content, and dry method silica produced by a dry method and containing almost no bound water. Dry method silica is further classified into crushed silica, fumed silica, fused spherical silica, etc., depending on the difference in production method. Among these, fused spherical silica is preferred from the viewpoints of low thermal expansion and flowability when filled into resin.
[0081] The average particle diameter of the inorganic filler (f) is preferably 0.1 to 10 μm, more preferably 0.3 to 8 μm, and even more preferably 0.3 to 3 μm. When the average particle diameter is 0.1 μm or more, the flowability when highly filled in the resin tends to be good, and when it is 10 μm or less, the probability of coarse particles being mixed in tends to be reduced, and the occurrence of defects caused by coarse particles tends to be suppressed. Here, the average particle diameter is the particle diameter at the point corresponding to 50% volume when a cumulative frequency distribution curve according to particle diameter is obtained with the total volume of the particles being 100%, and can be measured by a particle size distribution measuring device using a laser diffraction scattering method, etc. The inorganic filler (f) may be surface-treated with a coupling agent. The method of surface treatment with a coupling agent may be a method of performing a dry or wet surface treatment on the inorganic filler (f) before blending, or may be a so-called integral blend treatment method in which the inorganic filler (f) without surface treatment is blended with other components to form a composition, and then a silane coupling agent is added to the composition. Examples of the coupling agent include a silane-based coupling agent, a titanate-based coupling agent, and a silicone oligomer.
[0082] When the thermosetting resin composition contains an inorganic filler (f), the content thereof is preferably 20 to 300 parts by mass, more preferably 50 to 250 parts by mass, further preferably 70 to 200 parts by mass, and particularly preferably 100 to 160 parts by mass, relative to 100 parts by mass of the resin component in the thermosetting resin composition. When the content of the inorganic filler (f) is within the above range, the moldability and low thermal expansion properties are good.
[0083] <Other ingredients> The thermosetting resin composition of the present invention may contain, as necessary, an amine compound having an acidic substituent, an organic filler, a flame retardant, an ultraviolet absorber, an antioxidant, a photopolymerization initiator, a fluorescent brightening agent, an adhesion improver, etc., to the extent that the thermosetting properties are not impaired. These may be used alone or in combination of two or more.
[0084] The amine compound having an acidic substituent is not particularly limited as long as it has an acidic substituent such as a hydroxyl group, a carboxyl group, or a sulfonic acid group, but is preferably a compound represented by the following general formula (g). [ka] (In the formula, R g1 are each independently an acidic substituent, such as a hydroxyl group, a carboxyl group, or a sulfonic acid group; R g2 are each independently an aliphatic hydrocarbon group having 1 to 5 carbon atoms or a halogen atom, x is an integer of 1 to 5, and y is an integer of 0 to 4.
[0085] In the formula (g), R g1 From the viewpoints of solubility and reactivity, the acidic substituent represented by is preferably a hydroxyl group or a carboxyl group, and taking into consideration heat resistance, more preferably a hydroxyl group. x is an integer of 1 to 5, and is preferably an integer of 1 to 3, more preferably 1 or 2, and even more preferably 1, from the viewpoints of high heat resistance, low relative dielectric constant, high glass transition temperature, low thermal expansion and moldability. R g2 Examples of the alkyl group having 1 to 5 carbon atoms include a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, an isobutyl group, a t-butyl group, an n-pentyl group, etc. The alkyl group is preferably an alkyl group having 1 to 3 carbon atoms. R g2 The halogen atom represented by the formula (I) includes a fluorine atom, a chlorine atom, a bromine atom, an iodine atom, and the like. y is an integer of 0 to 4, and from the viewpoints of high heat resistance, low relative dielectric constant, high glass transition temperature, low thermal expansion and moldability, is preferably an integer of 0 to 3, more preferably an integer of 0 to 2, still more preferably 0 or 1, and particularly preferably 0. When x is an integer between 2 and 5, multiple R g1 may be the same or different. When y is an integer of 2 to 4, a plurality of R g2 may be the same or different.
[0086] Specific examples of amine compounds having an acidic substituent include m-aminophenol, p-aminophenol, o-aminophenol, p-aminobenzoic acid, m-aminobenzoic acid, o-aminobenzoic acid, o-aminobenzenesulfonic acid, m-aminobenzenesulfonic acid, p-aminobenzenesulfonic acid, 3,5-dihydroxyaniline, and 3,5-dicarboxyaniline. Among these, from the viewpoints of solubility and synthesis yield, m-aminophenol, p-aminophenol, o-aminophenol, p-aminobenzoic acid, m-aminobenzoic acid, and 3,5-dihydroxyaniline are preferred, from the viewpoint of heat resistance, m-aminophenol and p-aminophenol are more preferred, and from the viewpoint of low thermal expansion, p-aminophenol is even more preferred.
[0087] Examples of organic fillers include resin fillers made of polyethylene, polypropylene, polystyrene, polyphenylene ether resin, silicone resin, tetrafluoroethylene resin, etc.; and resin fillers having a core-shell structure having a rubber-like core layer made of an acrylate resin, a methacrylate resin, a conjugated diene resin, etc. and a glassy shell layer made of an acrylate resin, a methacrylate resin, an aromatic vinyl resin, a vinyl cyanide resin, etc.
[0088] Examples of the flame retardant include halogen-containing flame retardants containing bromine, chlorine, etc.; phosphorus-based flame retardants such as triphenyl phosphate, tricresyl phosphate, trisdichloropropyl phosphate, phosphate ester compounds, and red phosphorus; nitrogen-based flame retardants such as guanidine sulfamate, melamine sulfate, melamine polyphosphate, and melamine cyanurate; phosphazene-based flame retardants such as cyclophosphazene and polyphosphazene; and inorganic flame retardants such as antimony trioxide.
[0089] The ultraviolet ray absorbing agent may be, for example, a benzotriazole-based ultraviolet ray absorbing agent. Examples of the antioxidant include hindered phenol-based antioxidants and hindered amine-based antioxidants. Examples of the photopolymerization initiator include benzophenones, benzil ketals, and thioxanthone-based photopolymerization initiators. Examples of the fluorescent brightening agent include fluorescent brightening agents of stilbene derivatives. Examples of the adhesion improver include urea compounds such as urea silane, and the above-mentioned coupling agents.
[0090] The thermosetting resin composition may be in the form of a varnish in which each component is dissolved or dispersed in an organic solvent so that it can be easily used in the production of prepregs and the like.
[0091] Examples of the organic solvent include alcohol-based solvents such as methanol, ethanol, propanol, butanol, methyl cellosolve, butyl cellosolve, and propylene glycol monomethyl ether; ketone-based solvents such as acetone, methyl ethyl ketone, methyl isobutyl ketone, and cyclohexanone; ester-based solvents such as butyl acetate and propylene glycol monomethyl ether acetate; ether-based solvents such as tetrahydrofuran; aromatic solvents such as toluene, xylene, and mesitylene; nitrogen-containing solvents such as dimethylformamide, dimethylacetamide, and N-methylpyrrolidone; and sulfur-containing solvents such as dimethylsulfoxide. These may be used alone or in combination of two or more. Among these, from the viewpoint of the solubility of each component, methyl ethyl ketone, methyl isobutyl ketone, cyclohexanone, methyl cellosolve, and propylene glycol monomethyl ether are preferred, and methyl ethyl ketone is more preferred, and from the viewpoint of low toxicity, methyl isobutyl ketone, cyclohexanone, and propylene glycol monomethyl ether are more preferred. The solid content of the varnish is preferably 40 to 90% by mass, more preferably 50 to 80% by mass. When the solid content of the varnish is within the above range, it is possible to obtain a prepreg having an appropriate content of the thermosetting resin composition while maintaining good coatability. Here, the solid content refers to the residue remaining after excluding volatile components (e.g., organic solvents) from the components constituting the thermosetting resin composition.
[0092] (characteristic) A prepreg and a laminate are prepared using the thermosetting resin composition of the present invention by the method shown in the Examples, and the thermal expansion coefficient of the laminate measured by the method shown in the Examples is preferably 9.0 ppm / ° C. or less, more preferably 7.0 ppm / ° C. or less, and even more preferably 6.0 ppm / ° C. or less, from the viewpoint of low warpage. The lower limit of the thermal expansion coefficient is not particularly limited, but may be, for example, 3.0 ppm / ° C. or more, or 4.0 ppm / ° C. or more. Similarly, the flexural modulus is preferably 11.0 GPa or more, more preferably 12.0 GPa or more. There is no particular upper limit to the flexural modulus, but it may be, for example, 16.0 GPa or less, or 14.0 GPa or less. Similarly, from the viewpoint of heat resistance, the glass transition temperature is preferably 240° C. or higher, more preferably 250° C. or higher, even more preferably 260° C. or higher, particularly preferably 270° C. or higher, and most preferably 280° C. or higher. There is no particular upper limit to the glass transition temperature, but it may be, for example, 310° C. or lower, 300° C. or lower, or 290° C. or lower. Similarly, the adhesive strength (copper foil peel strength) is preferably 0.40 kN / m or more, more preferably 0.50 kN / m or more, and even more preferably 0.60 kN / m or more. There is no particular upper limit to the adhesive strength (copper foil peel strength), but it may be, for example, 1.0 kN / m or less, 0.90 kN / m or less, or 0.80 kN / m or less. Similarly, the desmear resistance was evaluated as follows: the weight loss after desmear treatment was 1.70 g / m 2 Less than 1.60 g / m is preferred. 2 Less than 1.50 g / m is more preferable. 2 The following is even more preferred:
[0093] [Prepreg] The prepreg of the present invention contains the thermosetting resin composition for printed wiring boards of the present invention. The prepreg of the present invention can be produced, for example, by impregnating a fiber base material with the thermosetting resin composition and semi-curing (B-stage) the composition by heating or the like. As the fiber substrate, any well-known material used in various laminates for electrical insulating materials can be used. Examples of the material include inorganic fibers such as E glass, S glass, low dielectric glass, and Q glass; organic fibers such as low dielectric glass polyimide, polyester, and tetrafluoroethylene; and mixtures thereof. In particular, from the viewpoint of dielectric properties, inorganic fibers are preferred, and low dielectric glass and Q glass are more preferred. These fiber substrates have the form of, for example, woven fabric, nonwoven fabric, roving, chopped strand mat, surfacing mat, and the like. The material and shape of the fiber substrate are appropriately selected depending on the intended use, performance, etc. of the molded product. If necessary, the fiber substrate may be made of one type of material and one type of shape, or may be made of two or more types of materials, or may have two or more types of shapes. The thickness of the fiber substrate is, for example, 10 μm to 0.5 mm, and from the viewpoint of enabling low warpage and high density wiring, it is preferably 10 to 100 μm, more preferably 10 to 80 μm, and even more preferably 15 to 50 μm. From the viewpoints of heat resistance, moisture resistance, processability, etc., it is preferable that these fiber substrates are surface-treated with a silane coupling agent or the like, or mechanically opened.
[0094] The content of the thermosetting resin composition in the prepreg of the present invention is, for example, 20 to 90 mass % of the total solid content of the prepreg, and from the viewpoint of improving low warpage properties and embeddability of wiring, it is preferably 50 to 85 mass %, and more preferably 60 to 80 mass %.
[0095] The thickness of the prepreg of the present invention is, for example, 10 μm to 0.5 mm, and from the viewpoint of reducing warping and enabling high-density wiring, it is preferably 10 μm to 100 μm, more preferably 10 μm to 80 μm, and even more preferably 15 μm to 50 μm.
[0096] The prepreg of the present invention can be produced, for example, by impregnating a fiber substrate with the thermosetting resin composition so that the content of the thermosetting resin composition in the prepreg falls within the above-mentioned range, and then drying by heating at a temperature of 100 to 200°C for 1 to 30 minutes to semi-cure (B-stage).
[0097] [Laminates, metal-clad laminates] The laminate of the present invention is a laminate containing the prepreg of the present invention. The laminate of the present invention can be obtained by laminating and molding the prepreg of the present invention. Specifically, the laminate can be produced by laminating and molding one sheet of the prepreg of the present invention or 2 to 20 sheets (preferably 2 to 8 sheets) of the prepreg of the present invention with metal foil on one or both sides of the laminate. This production method produces a laminate having an insulating layer formed using the prepreg of the present invention and metal foil on one or both sides of the insulating layer. There are no particular limitations on the metal foil as long as it is used for electrical insulating material applications. A laminate having a metal foil on one or both sides of the laminate is particularly called a metal-clad laminate. The molding conditions for producing the laminate and metal-clad laminate can be, for example, the same as those for laminates and multilayer boards for electrical insulating materials, and molding can be performed using a multistage press, a multistage vacuum press, a continuous molding machine, an autoclave molding machine, etc., at a temperature of 100 to 250°C, a pressure of 0.2 to 10 MPa, and a heating time of 0.1 to 5 hours. Also, the prepreg of the present invention can be combined with an inner layer wiring board and laminated to produce a laminate.
[0098] [Printed wiring board] The printed wiring board of the present invention contains the laminate (metal-clad laminate) of the present invention. More specifically, the printed wiring board of the present invention is obtained by processing the laminate (metal-clad laminate) of the present invention into a circuit. As a circuit processing method, known methods, that is, circuit forming processing methods by drilling, metal plating, etching of metal foil, etc., can be mentioned. In addition, a plurality of laminates processed by wiring through the prepreg of the present invention can be laminated and hot-pressed to form a multilayered board at once. After that, a multilayer printed wiring board can be manufactured by forming through holes or blind via holes by drilling or laser processing and forming interlayer wiring by plating or conductive paste.
[0099] [Semiconductor package] The semiconductor package of the present invention is obtained by mounting a semiconductor element on the printed wiring board of the present invention. The semiconductor package of the present invention can be manufactured by mounting a semiconductor chip, a memory, etc., at predetermined positions on the printed wiring board of the present invention. EXAMPLES
[0100] The present invention will now be described in more detail with reference to the following examples, which should not be construed as limiting the invention. The prepregs and copper-clad laminates obtained in the following examples were measured and evaluated for performance by the following methods.
[0101] (Characteristics of prepreg) (1) Storage stability (latency) Five of each prepreg were inserted into aluminum packs and vacuum packed. The first one was opened after 3 days, the second after 7 days, the third after 12 days, the fourth after 20 days, and the fifth after 30 days, and the presence or absence of voids was visually observed. Tables 1 and 2 show the number of days after opening when voids were observed. If no voids were observed after 30 days, it is indicated as ">30". The degree of vacuum during vacuum packing was 30 kPa, and the storage temperature was 25°C.
[0102] (Characteristics of copper clad laminate) (2) Formability A copper-clad laminate with a circuit processing with a residual copper ratio of 60% was prepared, and the prepreg obtained in each example was arranged on the wiring board so that the resin layer 1 (resin film A described later) of the prepreg was on the circuit side, and a copper foil with a thickness of 12 μm was arranged on the upper surface. Next, this was sandwiched between SUS mirror plates with a thickness of 1.8 mm and a square of 530 mm, and pressed for 90 minutes using a multi-stage vacuum press under conditions of a vacuum atmosphere, a heating rate of 3 to 5 ° C / min in the range of product temperature 60 to 160 ° C, a pressure of 2.5 MPa, and a maximum holding temperature of 200 to 220 ° C, to produce a copper-clad laminate. The copper foil of the obtained copper-clad laminate was removed by etching, and the appearance of the prepreg after curing was visually observed to evaluate the moldability according to the following evaluation criteria. A: No voids were observed. B: Voids were observed mainly around the edge. C: Voids were observed throughout the entire surface.
[0103] (3) Thermal expansion coefficient The copper-clad laminate obtained in each example was immersed in a copper etching solution to remove the copper foil, and an evaluation board with a length (X direction) of 5 mm, a width (Y direction) of 5 mm, and a thickness (Z direction) of 0.15 mm was prepared. Thermomechanical analysis was performed by compression using a TMA tester (manufactured by DuPont, product name: TMA2940). After mounting the evaluation board in the X direction on the device, measurements were performed twice in succession under the measurement conditions of a load of 5 g and a heating rate of 10°C / min. The average thermal expansion coefficient from 30°C to 100°C in the second measurement was calculated, and this was used as the value of the thermal expansion coefficient.
[0104] (4) Flexural modulus The copper-clad laminate obtained in each example was immersed in a copper etching solution to remove the copper foil, producing an evaluation board of 50 mm x 25 mm. The flexural modulus was measured using a Tensilon universal testing machine "RTC-1350A" (manufactured by Orientec Co., Ltd.) at a crosshead speed of 1 mm / min and a span distance of 20 mm. The higher the value, the higher the rigidity.
[0105] (5) Glass transition temperature (Tg) The copper-clad laminate obtained in each example was immersed in a copper etching solution to remove the copper foil, and an evaluation board with a length (X direction) of 5 mm, a width (Y direction) of 5 mm, and a thickness (Z direction) of 0.15 mm was prepared. Thermomechanical analysis was performed by compression using a TMA tester (manufactured by DuPont, product name: TMA2940). After mounting the evaluation board in the X direction on the device, measurements were performed twice in succession under the measurement conditions of a load of 5 g and a temperature rise rate of 10°C / min. The Tg indicated by the intersection of different tangents of the thermal expansion curve in the second measurement was obtained and used as an index of heat resistance. The higher the Tg, the better the heat resistance.
[0106] (6) Adhesive strength (copper foil peel strength) The copper-clad laminate obtained in each example was immersed in a copper etching solution to form an outer copper layer 3 mm wide, one end of which was peeled off at the interface between the outer copper layer and the insulating layer, gripped with a gripper, and peeled off in the vertical direction at a pulling speed of about 50 mm / min at room temperature using a tensile tester to measure the adhesive strength (copper foil peel strength). The higher the value, the better the adhesive strength.
[0107] (7) Desmear resistance (weight loss after desmear treatment) The copper foil was removed by immersing the copper-clad laminate in a copper etching solution to obtain a 40 mm × 40 mm evaluation board. The board was then immersed in a swelling solution, "Swelling Dip Securigant P" (aqueous solution of glycol ethers and sodium hydroxide, manufactured by Atotech Japan Co., Ltd.), at 60°C for 10 minutes, then in a roughening solution, "Concentrate Compact P" (aqueous solution of KMnO4: 60 g / L, NaOH: 40 g / L, manufactured by Atotech Japan Co., Ltd.) at 80°C for 20 minutes, and finally in a neutralizing solution, "Reduction Shoreusin Securigant P" (aqueous solution of sulfuric acid, manufactured by Atotech Japan Co., Ltd.) at 40°C for 5 minutes, and then dried at 80°C for 10 minutes to perform a desmear treatment. Weight loss after desmearing relative to dry weight before desmearing (g / m 2 The smaller the weight loss after the desmear treatment, the better the desmear resistance.
[0108] Examples 1 to 8, Comparative Examples 1 to 6 The components shown below were mixed in the proportions shown in Tables 1 or 2 (the amounts of the components in the tables are calculated as solids in the case of solutions), and a varnish with a solids concentration of 65% by mass was prepared using methyl ethyl ketone as a solvent. Next, this varnish was impregnated and coated on a T-glass cloth with a thickness of 25 μm, and dried by heating at 130° C. for 10 minutes to obtain a prepreg with a thermosetting resin composition content of 68% by mass. Four sheets of this prepreg were stacked, 3 μm electrolytic copper foil was placed on top and bottom, and pressed for 90 minutes at a pressure of 2.5 MPa and a curing temperature shown in Table 1 or Table 2 to obtain a copper-clad laminate. The obtained copper-clad laminate was evaluated according to the above-mentioned methods. The results are shown in Tables 1 and 2.
[0109] The components used in each example are shown below. [Phosphonium salt (a) with carboxylate anion as counter ion] TBP3S: Tetrabutylphosphonium hydrogenhexahydrophthalate represented by the following formula, produced according to the method described in Production Example 1 of Japanese Patent No. 5191131: [ka] BTBP pyromellitic acid: Bis(tetra-n-butylphosphonium) dihydrogen pyromellitate represented by the following formula, produced according to the method described in Production Example 2 of WO 2018 / 021548. [ka] (In the above formula, Bu represents an n-butyl group.)
[0110] [Curing accelerator (e) other than phosphonium salt (a)] C11Z: 2-Undecylimidazole (product name, manufactured by Shikoku Chemical Industry Co., Ltd.) 2PZ: 2-phenylimidazole (product name, manufactured by Shikoku Chemical Industry Co., Ltd.) TPP: Triphenylphosphine [product name, manufactured by Hokko Chemical Industry Co., Ltd.]
[0111] [Maleimide compound (b) having at least two N-substituted maleimide groups] BMI: Bis(4-maleimidophenyl)methane (product name, manufactured by K.I. Kasei Co., Ltd.) BMI-4000: 2,2-bis[4-(4-maleimidophenoxy)phenyl]propane (manufactured by Daiwa Chemical Industry Co., Ltd., product name) BMI-3000: m-phenylene bismaleimide [manufactured by Daiwa Chemical Industry Co., Ltd., product name]
[0112] [Thermoplastic elastomer (c)] SG-P3: Epoxy group-containing acrylic polymer (manufactured by Nagase Chemtex Corporation, product name: Teisan Resin (registered trademark) SG-P3, weight average molecular weight: 850,000)
[0113] [Thermosetting resin (d)] NC-3000: Biphenyl aralkyl type epoxy resin [product name, manufactured by Nippon Kayaku Co., Ltd.]
[0114] [Inorganic filler (f)] Spherical fused silica [Admatechs Co., Ltd., product name, average particle size: 0.5 μm]
[0115] [Table 1]
[0116] [Table 2]
[0117] From Table 1, it can be seen that the thermosetting resin compositions prepared in the examples have excellent heat resistance, low thermal expansion, and high elastic modulus, as well as high adhesive strength and desmear resistance, and are suitable for printed wiring board applications. Furthermore, in Examples 2 and 4, the compositions were cured at a curing temperature (180°C) lower than the general curing temperature (220°C or higher) of polyimide resins, but the properties of the laminate were sufficient, so it is considered that the compositions were sufficiently cured. In addition, although the thermosetting resin compositions used in Examples 2 and 4 are highly active so that curing proceeds sufficiently at low temperatures, they have high storage stability at room temperature and are highly industrially useful. On the other hand, the thermosetting resin compositions prepared in each Comparative Example shown in Table 2 are inferior to the Examples in at least one of high adhesive strength and desmear resistance. In Comparative Example 3, when the amount of the curing accelerator was increased, the moldability was significantly reduced. In Comparative Example 4, when a highly active curing accelerator was used, the storage stability was reduced.
[0118] (Verification of the reason for excellent low-temperature curing properties) As described above, in Examples 2 and 4, the polyimide resin could be sufficiently cured at a curing temperature (180°C) lower than the general curing temperature (220°C or higher) of the polyimide resin. In order to analyze the reason for this, a differential scanning calorimeter (DSC) analysis was performed on a thermosetting resin composition consisting of a combination of 15 mmol of the BMI and 0.06 mmol of each curing accelerator listed in Table 3 below. Specifically, a differential thermal calorimeter (manufactured by TA Instruments, product name: Q200 type differential thermal calorimeter) was used to measure the reaction start temperature and peak temperature when the temperature was raised from 25°C to 340°C at a heating rate of 10°C / min under a nitrogen atmosphere, and the temperature difference (ΔT) between them was calculated. The reaction start (curing start) temperature was taken as the temperature at the intersection of the tangent to the maximum slope point of the curing heat generation peak and the baseline in the obtained DSC curve. The results are shown in Table 3.
[0119] [Table 3]
[0120] From Table 3, when the phosphonium salt (a) (TBP3S, BTBP pyromellitic acid) used in the present invention is blended with BMI, the peak temperature is lower and the temperature difference (ΔT) from the reaction start temperature to the peak temperature is also smaller than when no curing accelerator is blended or when other curing accelerators (TPP, C11Z) are blended. It is believed that the fact that the time from the reaction start to the peak temperature is reached quickly and the peak temperature is low leads to the result of excellent low-temperature curing properties. [Industrial Applicability]
[0121] The thermosetting resin composition of the present invention has excellent heat resistance, low thermal expansion property, and high elastic modulus as well as high adhesive strength and desmear resistance. Therefore, prepregs and laminates obtained by using the thermosetting resin composition can be suitably used for electronic component applications such as multilayer printed wiring boards and semiconductor packages.
Claims
1. A thermosetting resin composition for printed wiring boards, comprising: (a) a phosphonium salt having a carboxylate anion as a counter ion; (b) a maleimide compound having at least two N-substituted maleimide groups; and (c) a thermoplastic elastomer, the content of the component (a) is 0.01 to 1.0 parts by mass per 100 parts by mass of the resin component in the thermosetting resin composition, The thermosetting resin composition for printed wiring boards has a content of the thermoplastic elastomer (c) of 0.1 to 50 parts by mass per 100 parts by mass of the resin component in the thermosetting resin composition.
2. The thermosetting resin composition for printed wiring boards according to claim 1, wherein the component (a) contains a phosphonium salt consisting of a phosphonium cation represented by the following general formula (a1) and an anion residue of a polycarboxylic acid represented by any one of the following general formulas (a2) to (a4): 【Chemistry 1】 (In formula (a1), R 1 ~R 4 are each independently an alkyl group having 1 to 16 carbon atoms or a substituted or unsubstituted phenyl group. 【Chemistry 2】 (In formula (a2), R 5 is a methylene group or an ethylene group, R 6 ~R 9 are each independently a hydrogen atom, an alkyl group having 1 to 4 carbon atoms, or a carboxyl group. 【Chemistry 3】 (In formula (a3), R 10 ~R 13 are each independently a hydrogen atom, an alkyl group having 1 to 4 carbon atoms, or a carboxyl group. 【Chemistry 4】 (In formula (a4), R 14 is an alkyl group having 1 to 10 carbon atoms. n is an integer of 0 to 2.
3. 3. The thermosetting resin composition for printed wiring boards according to claim 1 or 2, wherein the thermoplastic elastomer (c) is at least one selected from the group consisting of a styrene-based thermoplastic elastomer, an olefin-based thermoplastic elastomer, a urethane-based thermoplastic elastomer, a polyester-based thermoplastic elastomer, a polyamide-based thermoplastic elastomer, an acrylic-based thermoplastic elastomer, a silicone-based thermoplastic elastomer, and derivatives thereof.
4. The thermosetting resin composition for printed wiring boards according to any one of claims 1 to 3, further comprising a thermosetting resin (d).
5. The thermosetting resin composition for printed wiring boards according to any one of claims 1 to 4, further comprising an inorganic filler (f).
6. A prepreg comprising the thermosetting resin composition for printed wiring boards according to any one of claims 1 to 5.
7. A laminate comprising the prepreg according to claim 6.
8. A printed wiring board comprising the laminate according to claim 7.
9. A semiconductor package comprising the printed wiring board according to claim 8 and a semiconductor element mounted thereon.
Citation Information
Patent Citations
Low-thermal-expansion pressure molding resin composition
JP1993148343A
Thermosetting resin composition, prepreg, film with resin, laminate sheet, multilayer printed circuit board and semiconductor package
JP2015224304A
Thermosetting resin composition, and prepreg, film with resin, laminate, multilayer printed wiring board and semiconductor package using the same
JP2016030757A
Thermosetting resin composition
JP2018065903A
Thermosetting resin composition
JP2018065904A